(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The research aims to identify the reality of social responsibility practices among customers of telecommunications companies in Iraq with a search for social responsibility initiatives pursued by the most important telecommunications companies that are active in Iraq, where the data that was taken from Khatam Telecom Company (Zain) and Asiacell related to the level of spending on social responsibility, which is reflected in maximizing the profits of those companies, and the research reached several results, including the presence of indicators of customer interest in the services of telecommunications companies in Iraq with social responsibility, except It is noticeable that the social practices that are adopted can be considered tactical measures resorted to by customers at certain times such as national and religious holidays , and that Zain’s social expenses have a significant impact on increasing the company’s profits, unlike the expenses of Asa Cell, which turned out to not affect the increase in the company’s profits throughout the research years 2011-2021, which requires Asa Cell to use another type of expense that contributes to increasing profits.